Pemanfaatan Digital Marketing untuk Komunikasi Bisnis UMKM di Desa Sumber Rejo Kabupaten Batubara Sumatera Utara - Utami, Rizkika; Alindra, Devi Alvionita; Siregar, Feby Yoana; Purba, Christin Agustina; Anggoro, Muhammad Agung (Jurnal Pengabdian Masyarakat Inovasi, 2025)
The utilization of digital technology is a key factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the global economic era. This community service research aims to empower MSME actors in Sumber Rejo Village, Batubara Regency, North Sumatra, through the optimization of digital marketing as a means of business communication. The partners consist of 26 MSMEs producing "keripik pisang gosong" (caramelized banana chips) and "emping" (melinjo crackers), who previously relied on conventional marketing methods. The implementation method utilized a participatory approach, including needs identification, technical training (content creation, social media management, and e-commerce registration), and intensive mentoring for 1.5 months. The results show a significant increase in digital literacy and technical skills among participants. A total of 18 MSMEs successfully expanded their market reach outside the region and reported a 15-30% increase in sales. Despite facing challenges such as limited internet access and technological adaptation issues among older participants, the program successfully laid the foundation for digital transformation in rural areas. In conclusion, the sustainable integration of digital marketing strategies and the formation of local digital communities are essential to maintain business consistency. This program recommends infrastructure support from the local government to support the sustainability of the MSME digital economy in Batubara Regency.